Abuse of Human Rights in The Neoliberal World Order: The Case of Israel Palestine Conflict - Britee Adhikary; Poushali Chatterjee, (Indian Journal of Social Science and Literature (IJSSL), 2024)
The rights which are entitled to human beings, are crucial for their existence and are formulated with the intention of safeguarding their life, personal liberty and dignity are referred to as human rights. The traditional notion of human rights and security perceived them as antithetical and separate concepts whereas the current idea propagates the interlinkage between the two and highlights the need to preserve human rights in order to enforce security. Neoliberalism seeks to reduce the role of the state including to diminish its social and welfare responsibilities which affects the protection and implementation of human rights. Thus, a pertinent question is raised: What aspects of neoliberalism are abusive of human rights in the contemporary international structure? This paper takes up the case study of the Israel-Palestine conflict, which dates back to the nineteenth century and analyses it from the perspective of human rights conservation. Israel refuses to give the status of ‘rightful sovereigns’ to the Palestinians residing in the West Bank and Gaza and therefore, believes that they are not entitled to any protection bestowed by the international humanitarian laws. This research further takes into account the aspect of human rights in the U.S. policies concerning Israel. The U.S. has been projecting itself as the torchbearer of liberalism and individual rights in the contemporary neoliberal world order. Yet, it provides military and economic support to Israel and virtually remains silent in its wrongful claims over Palestinian territories. The contemporary world order has seen different countries adopting rightist policies, excluding regional identities and promoting the concept of a homogenized society. The abuse of human rights which these circumstances bring about become equally pertinent as the newest threat to individual security and consequently affects the international socio-political domain.